2022
DOI: 10.1097/ijg.0000000000002052
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of the Preserflo Microshunt With Mitomycin C for the Treatment of Open Angle Glaucoma

Abstract: Précis: The Preserflo Microshunt (PSM) is a safe and effective glaucoma microfiltering implant that significantly reduces the intraocular pressure (IOP), either alone or in combination with phacoemulsification, during the first year after surgery. Purpose:The purpose of this study was to assess the safety and efficacy of the PSM for the treatment of open angle glaucoma with 0.2 mg/mL mitomycin C, either alone or in combination with cataract surgery. Methods:A retrospective, open-label study of 64 eyes with pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
35
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 41 publications
5
35
3
Order By: Relevance
“…The literature search yielded a total of 311 articles of which 14 studies (including 1213 PRESERFLO MicroShunt surgeries) were included in the current study and considered eligible for the meta-analysis ( Table S1, Figure S2 ) [ 9 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Follow-up ranged from 12 months to 72 months.…”
Section: Resultsmentioning
confidence: 99%
“…The literature search yielded a total of 311 articles of which 14 studies (including 1213 PRESERFLO MicroShunt surgeries) were included in the current study and considered eligible for the meta-analysis ( Table S1, Figure S2 ) [ 9 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Follow-up ranged from 12 months to 72 months.…”
Section: Resultsmentioning
confidence: 99%
“…Given that the most commonly observed bleb after PreserFlo Microshunt implantation is localized beneath Tenon’s capsule posterior to the limbus, as reported by Ibarz Barberá et al 23 in 2022, and considering the deep positioning of the device, an open revision seems to be a suitable approach 22 . It allows the removal of scar tissue surrounding the tube, which is usually responsible for stopping the flow 1 …”
Section: Discussionmentioning
confidence: 99%
“…Similar, newer surgical procedures, such as PreserFlo Microshunt implantation, have also demonstrated a notable percentage of bleb fibrosis, often necessitating additional surgical interventions. Bleb fibrosis occurs among 3.4% after 3 months, 15.6% after 9 months, 19.0% after 12 months, and up to 53% after 4 years after PreserFlo Microshunt implantation 1,7,18–21 . Up to now, there is no recommended surgical procedure in case of bleb fibrosis for PreserFlo Microshunt implantation due to the lack of data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 11 Clinical studies have shown that the overall success rate of the PreserFlo MicroShunt is 70% after approximately 1 year. 12 , 13 Although effective in reducing IOP, surgeries may still fail due to the formation of fibrosis, even with the additional usage of MMC. 14 , 15 Patients will often require additional IOP-lowering medications or surgeries to reach the desired low IOP level.…”
Section: Introductionmentioning
confidence: 99%